Implementation of Indonesian Law Policy No. 33/2014 on Halal Product Guarantee (JPH) in Makassar City - Safaruddin Safaruddin (Universitas Muslim Indonesia, 2021)
Development in Indonesia has had a significant impact on society. Along with that, changes in the welfare of the community both increased and decreased have also impacted on lifestyle changes and the way people view, especially in terms of food and beverage consumption. The purpose of this research is to review the implementation of the Law Policy, No. 33/2014 on Halal Product Guarantee. The research method used is a combination of riview literature and long observation on the implementation of the Law policy, No. 33/2014 on Halal Product Guarantee. With the enacting of the Act, it is expected that all products circulating in Indonesia can have halal certificate. Makassar is a metropolitan city with a population of more than 1.6 million people. They are the majority of Muslims. The city is a multi-ethnic or multicultural type with various ethnic groups that live in it including Bugis, Makassar, Toraja, Mandar, Buton, Java, and Chinese. Halal awareness is rated still low this in the first evidence, entrepreneurs do not care. Second, customers are not very concerned about the absence of halal certification in the culinary businesses they visit. Third, the management of certificates issued by the Indonesian Ulama Council (MUI) is quite expensive. Fourth, the lack of socialization and information has led to a lack of knowledge and awareness of businesses. Data every year that shows halal certification is still very minimal